Viroids and Satellites - Hadidi, A. (Academic Press is an imprint of Elsevier, 2017)
'Viroids and Satellites' describes plant diseases and their causal agents while also addressing the economic impact of these diseases. It discusses various strategies for state-of-the-art methods for the detection and control of pathogens in their infected hosts and provides pivotal information from the discovery of viroids through the analysis of their molecular and biological properties, to viroid pathogenesis, host interactions and RNA silencing pathways.